In situ epitaxial growth of GdF3 on NaGdF4:Yb, Er nanoparticles. Issue 12 (6th November 2017) - Li, Jiangfeng; Jia, Yunling; Xu, Yuejiao; Yang, Hui; Sun, Ling-dong; Yan, Chun-hua; Bie, Li-jian; Ju, Jing
Abstract : By electron-beam irradiation of TEM, GdF3 (020) was epitaxially grown on the interface of NaGdF4 (111). Abstract : NaGdF4 is a well-known up-conversion material with potential applications in lasers and biolabels and used to be known as a thermally stable material bearing harsh natural conditions. In this work, a TEM electron beam was found to be able to manipulate the morphology of cubic-NaGdF4, changing it from solid nanoparticles to porous materials with nano-sized vacancies by electron beam irradiation. Electron beams also induce a structure change from cubic-NaGdF4 to GdF3 . By controlling the current density of the TEM electron beam, the in situ epitaxial growth behavior of GdF3 (020) was observed at the NaGdF4 (111) interface. Structural correlations between two compounds were discussed to understand the epitaxial growth with a large lattice mismatch. These findings suggest a TEM electron beam can be used not only as an imaging tool, but also as an alternative paradigm for manipulating matter.